In vitro enzyme activity and in vivo healing activity of the protein extract from pineapple peel - Denise Alvarenga Rocha; Estela de Rezende Queiroz; Lucimara Nazaré Silva Botelho; Rodrigo Martins Fráguas; Cláudia Mendes dos Santos; Celeste Maria Patto Abreu; Raimundo Vicente de Sousa (Acta Scientiarum. Biological Sciences, 2019)
The pineapple is a fruit that has wide acceptance worldwide both in natural form, as industrialized. Your peel is a residue generated by food industries and from this residue can obtain a protein extract which is a good source of bromelain. This study aimed to obtain a protein extract from pineapple peel, evaluate its enzyme activity and its healing properties in skin lesions in rats. Seven animal groups were used: control, treated with 5% of protein extract, 10% of protein extract and pure protein extract; 5% of commercial bromelain, 10% of commercial bromelain and pure commercial bromelain. The animals were subjected to a tissue incision and treated for 21 days. Proteolytic and specific activities of the protein extract were 1.30 U mg-1 and 45 x 10-3 U µg-1 and, for commercial bromelain, 1.04 U mg-1 and 6 x 10-3 U µg-1, respectively. In the histology of the lesion, there was no significant difference between the control and treated groups; however, macroscopically, the prepared topical formulations assisted in the recovery of skin lesions, providing a significant reduction in their width, in the groups treated with pure protein extract, 5 and 10% commercial bromelain, and pure bromelain.